Cololejeunea tianmuensis, a new epiphyllous species of Cololejeunea (Lejeuneaceae, Marchantiophyta) from Zhejiang, China - Dai, Zun; Tang, Xia; Tu, Shu-Wen; Zhuang, Li-Jie; Zhu, Mao-Jie; Zhao, Ming-Shui; Zhang, Zhao-Chen; Wang, Jian (Phytotaxa, 2019)
Cololejeunea tianmuensis sp. nov. is described and illustrated from Tianmushan National Nature Reserve, Lin’an City, Zhejiang Province, China. The new species is similar to C. magnistyla and C. japonica, but differs mainly in its variable stylus which ranges from one to five cells in length and one to two cells in width on the same stem. The conservation of the new species is also discussed here.